2001
DOI: 10.1007/s004380000366
|View full text |Cite
|
Sign up to set email alerts
|

The mitochondrial inner membrane protein Lpe10p, a homologue of Mrs2p, is essential for magnesium homeostasis and group II intron splicing in yeast

Abstract: The yeast ORF YPL060w/LPE10 encodes a homologue of the mitochondrial protein Mrs2p. These two proteins are 32% identical, and have two transmembrane domains in their C-terminal regions and a putative magnesium transporter signature, Y/F-G-M-N, at the end of one of these domains. Data presented here indicate that Lpe10p is inserted into the inner mitochondrial membrane with both termini oriented towards the matrix space. Disruption of the LPE10 gene results in a growth defect on non-fermentable substrates (peti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
68
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(69 citation statements)
references
References 22 publications
(53 reference statements)
1
68
0
Order By: Relevance
“…Previous reports indicated that both the Mrs2 and the Lpe10 proteins were essential for Mg uptake by mitochondria, as lpe10 and mrs2 mutants displayed a similar decrease in mitochondrial Mg content (Gregan et al 2001a;Kolisek et al 2003). To determine the effect of these mutations on whole-cell Mg content, we grew strains carrying combinations of mnr2, lpe10, and mrs2 mutations in Mgreplete and -deficient conditions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous reports indicated that both the Mrs2 and the Lpe10 proteins were essential for Mg uptake by mitochondria, as lpe10 and mrs2 mutants displayed a similar decrease in mitochondrial Mg content (Gregan et al 2001a;Kolisek et al 2003). To determine the effect of these mutations on whole-cell Mg content, we grew strains carrying combinations of mnr2, lpe10, and mrs2 mutations in Mgreplete and -deficient conditions.…”
Section: Resultsmentioning
confidence: 99%
“…NP174, NP180, NP193, and NP201 were generated by sequential transformation of DY1514 with the insert of pmnr2SpHIS5 and a tfp1TKAN R PCR product, followed by sporulation. NP103, NP107, and NP112 were derived by transformation of DBY747, and lpe10D-1 and mrs2D-2 (Gregan et al 2001a) with the mnr2TKAN R PCR product. AAS and inductively coupled plasma-mass spectrometry: Measurement of total cell-associated Mg was routinely performed using AAS.…”
Section: Methodsmentioning
confidence: 99%
“…MRS2 encodes a mitochondrial inner membrane protein that functions as a magnesium transporter (Bui et al 1999;Gregan et al 2001) and is required for splicing of mito- cox2 (1,15,(89)(90)(91) cox2 (1,(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(89)(90)(91) cox2 (1,(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(89)(90)(91) cox2 (1,(17)(18)(19)(20)(21)(22)(23)(24)(25)(89)(90)(91) cox2 (1,(18)(19)(20)(21)(22)(23)(24)(25)(89)(90)(91) cox2 (1,…”
Section: The Inhibitory Element In Codons 15-25 Is Embedded In the Mrmentioning
confidence: 99%
“…Moreover, several metal ion binding sites have been located in the active site (38 -40), and a two-metal ion mechanism (41,42) has been suggested to underlie intron catalysis (43,44). In-cell studies establishing a correlation between the intracellular Mg 2ϩ concentration and the frequency of splicing and retrohoming buttress the relevance of Mg 2ϩ for group II intron catalysis (45)(46)(47)(48). The importance of the identity of the divalent metal ions bound to the intron is underscored by the finding that the presence of Mn 2ϩ can lead to a shift of the cleavage site (49) and that already low amounts of Ca 2ϩ decrease the turnover rate by 50% in the Sc.ai5␥ intron (50).…”
mentioning
confidence: 99%